Pertumbuhan dan Tingkat Kelangsungan Hidup Donor Transplan Karang Acropora hyacinthus Berdasarkan Ukuran Panjang Awal Fragmen yang Berbeda - AAK Aswan Deva; I Gusti Ngurah Putra Dirgayusa; Widiastuti Widiastuti (Journal of Marine and Aquatic Sciences, 2021)
Coral reefs play significant roles in both aspects of ecology and economy. However its status in Indonesian reefs is mainly moderate to poor condition. One of the alternative way to rehabilitate the damaged coral reef is coral transplantation. Acropora hyacinthus is one of export comodities for ornamental aquarium and important component of reef builder organisms. Studies showed that fragmentation causes stress on the coral donor as indicated by the excessive mucus production which in turn may affect the survival of the coral donors. This study aims to determine the growth and survival rates of donors based on the initial fragment sizes. A total of 5 coral donors of A. hyacinthus with relatively similar branch were fragmented into initial sizes of 30, 50 and 70 mm and the rests were controls. The growth was indicated by the increase in length which measured every two weeks for 12 weeks. The results showed that the absolute growth of coral donors were significantly different among initial sizes. The survival rate in the initial length of 30 mm (100%) was higher than those in 50 mm (80%) and 70 mm (80%).